Occurrence patterns of the endangered Yellow Cardinal Gubernatrix cristata in north-east Argentina: only in savannahs and at sites away from roads - Reales, César Fabricio (2023)
The endangered Yellow Cardinal Gubernatrix cristata is under pressure from habitat loss and from capturing for the cage bird trade. In north-east Argentina it is known to be associated with the Espinal ecoregion, but no information was available on habitat selection within this ecoregion. In Entre Ríos province, Argentina, we first sampled Yellow Cardinal presence in four environments: Espinal savannahs, Espinal open woodlands, riparian woodlands, and agricultural fields. Yellow Cardinals were only detected in savannahs. In a second set of surveys, transects were surveyed at sites with known presence of Yellow Cardinals and were placed within savannahs as well as nearby in open forests of only slightly different physiognomy. Yellow Cardinals were again only detected in savannahs. Tree density, shrub cover and height of herbaceous layer were lower in savannahs than in open woodlands. Ground-foraging Yellow Cardinals in savannahs foraged exclusively in grass patches with short grass of 3˗12 cm height. Such short grass occurred in 75% of spots of savannahs sites, but only in 48% of open woodlands. Savannah sites with Yellow Cardinals were significantly further away from permanent roads than sites without Cardinals, likely a reflection of capture pressure near roads. We recommend establishing additional protected areas with a high proportion of savannah patches and with limited or no road access. The short grass used by foraging Yellow Cardinals requires maintenance through grazing. Rewilding with native herbivores in protected areas is preferable to attain natural herbivory, but during the initial stages of rewilding, cattle and sheep grazing are essential to avoid tree and shrub proliferation in savannahs. The Yellow Cardinal can also persist on private lands with Espinal vegetation under sustainable livestock grazing. Frequent and effective patrolling and road controls are essential to reduce illegal capturing.